Formulation of minimum medium for bacteriocin production by Lactobacillus plantarum strains - Mazlan, Nurzafirah (2013)
The production of bacteriocin, an antimicrobial compound produced by lactic acid bacteria, has been reported to be affected by several environmental factors including carbon and nitrogen sources. The selective de Mann Rogosa Sharpe (MRS) medium is the common medium that extensively used to cultivate Lactobacillus sp. and for bacteriocin production. The main disadvantage of employing this complex media is that it is costly for media application. The minimum requirement of nutrient is essential to be determined to produce bacteriocin economically. Therefore, the main objective of this study was to formulate minimum medium composition for the six strains of L. plantarum to attain comparable bacteriocin activity that obtained with MRS medium. A total of 20 g/L of carbon source and 22 g/L of nitrogen source were employed in each modified medium, which was similar to the amount of carbon and nitrogen source in MRS media. The results obtained in this study showed that yeast extract was the best nitrogen source as compared to other nitrogen sources when combined with either molasses or glucose for the production of bacteriocin by L.plantarum strains, suggesting that molasses and glucose are compatible carbon sources. In addition, subsequent inclusion of meat extract and/or peptone into the basic designed growth medium did not increase bacteriocin activity further. Similar results were obtained when more than two different nitrogen sources were combined in the basic growing medium, implying that both meat extract and peptone were not essential nitrogen sources for the production of bacteriocin by L. plantarum strains. However, the requirement of trace elements, minerals and other nutrients for bacteriocin production was strain dependent. Moreover, the bacteriocin production profile was dependent on the carbon source that included in growth medium. L. plantarum I-UL4 was chosen as a model to study the growth and bacteriocin production in 3 L bioreactor and result showed that both bacteriocin and cell mass were produced earlier as compared to static growth method. Generally, the results obtained in this study indicated that the elimination of unnecessary nutrient elements as found in selective MRS medium is feasible to reduce the production cost of bacteriocin by L. plantarum substantially.